If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3 + 3 = 7 + 4 Reorder the terms: 3 + 3 + X = 7 + 4 Combine like terms: 3 + 3 = 6 6 + X = 7 + 4 Combine like terms: 7 + 4 = 11 6 + X = 11 Solving 6 + X = 11 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + X = 11 + -6 Combine like terms: 6 + -6 = 0 0 + X = 11 + -6 X = 11 + -6 Combine like terms: 11 + -6 = 5 X = 5 Simplifying X = 5
| 7x+2=4x+x+1+2x+1 | | (-8-3)-5(2-5)= | | 6(x+12)=108 | | 5d+13=3 | | (1-n)(2n-3)=0 | | 5x+14y=86 | | 3t+3=t+3 | | -12/13/X/4= | | f(x)=20(1.3) | | f=-3.5+2x | | [(-2)+7-(-5)]+[-4-(-10)]= | | -9N-6+2N= | | 8xs+40=16 | | -x=-2y-4 | | 3x((17-9x)-(16x-10))=30-23x | | 5x+3=168 | | y-2.8=7.24 | | 2x+3y=229 | | 0=3r^2-8r+1 | | 8x-1x=2 | | 6y^2-13y=6 | | 3x+9=-54-6 | | 18+3(x-4)+6= | | Y-(-2)=6/1(x-2) | | 10+12=14y-1-13y | | 3.25g+1.25g=81 | | 15X+4=10X+21 | | ay=5y+16 | | 12d=11 | | 15-3(x+5)-2= | | c-13=-1 | | 4(3p+2)-5(6p-1)=2(p-8)-6(7p-4) |